National museums and the origins of nations : emotional myths and narratives - Watson, Sheila (London : Routledge, 2021)
National Museums and the Origins of Nations provides the first international survey of origins stories in national museums and examines the ways in which such museums use the distant past as a vehicle to reflect the concerns of the political present. Offering an international comparison of institutions in China, North and South America, the Middle East, Europe and Australia, the book argues that national museums tell us more about what sort of community a nation wishes to be today, than how and why that nation came into being. Watson also reveals the ways in which narrative and exhibition design attempt to engage the visitor in an emotional experience designed to promote loyalty to, and pride in, the nation, or to remind visitors who are not citizens that they do not belong. These narratives of origin are, it is claimed, based on so-called factual accuracies, but this book reveals that they are often selective, emotional and rarely critiqued within institutions. At a time when nationalism is very much back on the political agenda, this book highlights how museums reflect current political and social concerns. National Museums and the Origins of Nations will appeal to academics and students engaged in the study of museums, heritage, politics, nationalism and history.--
OCLC-licensed vendor bibliographic record.
Keywords: National museums; Cultural property -- Political aspects; Nationalism; POLITICAL SCIENCE / Political Ideologies / Nationalism; POLITICAL SCIENCE / Civics & Citizenship